Superscan-Like Pattern on 18F-Choline PET/CT in a Patient With Essential Thrombocythemia. (22nd March 2023) - Urso, Luca; Nieri, Alberto; Borgia, Francesca; Malorgio, Antonio; Bartolomei, Mirco
Abstract: Few clinical and preclinical articles reported the potential usefulness of 18 F-choline PET/CT in several hematological proliferative diseases. We report and incidental finding of a superscan-like pattern in a patient affected by essential thrombocythemia (ET), performing 18 F-choline PET/CT for a biochemical recurrence of prostate cancer. The mild elevation of PSA values and the negativity of subsequent 68 Ga-PSMA-11 PET/CT allowed to correlate the diffuse skeletal uptake detected on 18 F-choline PET/CT to the underlying hematologic disease, rather than to a prostate cancer relapse.